2017
DOI: 10.1103/physrevb.96.184107
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of dynamically disordered tetragonal platelets in the relaxor ferroelectric 0.964Na1/2Bi1/2TiO30.036

Abstract: The local dynamics of the lead-free relaxor 0.964Na 1/2 Bi 1/2 TiO 3 − 0.036BaTiO 3 (NBT-3.6BT) have been investigated by a combination of quasielastic neutron scattering (QENS) and ab initio molecular dynamics simulations. In a previous paper, we were able to show that the tetragonal platelets in the microstructure are crucial for understanding the dielectric properties of NBT-3.6BT [F. Pforr et al., Phys. Rev. B 94, 014105 (2016)]. To investigate their dynamics, ab initio molecular dynamics simulations were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…Beyond the second MPB at x ~7.5%, the tetragonal symmetry changes to P 4 mm , where the A-site atoms and Ti exhibit a robust cooperative off-centring along [001]. We think that the maximal piezoelectric properties reported for the ceramics with around x = 6–7% 21,23,27,34,35 are directly related to the ferrielectric-mediated MPBs.…”
Section: Composition-driven Phase Diagrammentioning
confidence: 99%
“…Beyond the second MPB at x ~7.5%, the tetragonal symmetry changes to P 4 mm , where the A-site atoms and Ti exhibit a robust cooperative off-centring along [001]. We think that the maximal piezoelectric properties reported for the ceramics with around x = 6–7% 21,23,27,34,35 are directly related to the ferrielectric-mediated MPBs.…”
Section: Composition-driven Phase Diagrammentioning
confidence: 99%
“…Another TEM study showed that the volume fraction of tetragonal polar nanoregions (PNRs) increases as the BT content increases toward the MPB [9]. The relation between the local structure and the relaxor behavior, as well as the relation between the local structure and the average structure, has been considered as an important subject and investigated intensively [13,14,15]. A more recent NMR study has suggested that the octahedral tilting disorder is responsible for the relaxor behaviors of NBT- x BT [16].…”
Section: Introductionmentioning
confidence: 99%